Metal matrix composite grinding ball
By using conventional casting technology to manufacture ceramic metal composite particle shells with high ceramic particle content and low porosity in grinding balls, the problem of insufficient wear resistance of existing grinding balls under high impact stress and abrasion conditions is solved, and the problem of insufficient wear resistance of existing grinding balls under high impact stress and abrasion conditions is achieved. Efficient manufacturing and good mechanical properties of ceramic metal composites.
Patent Information
- Application Number
- CN202380040155.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-24
AI Technical Summary
It is difficult for existing grinding balls to achieve high wear resistance and ductility at the same time under high impact stress and abrasion conditions, and the manufacturing process of ceramic metal composite materials has problems of high porosity and high cost.
The ceramic reinforced grinding ball with a core shell structure is manufactured using conventional casting technology. The shell is composed of a three-dimensional interconnection network of periodic alternating ceramic metal composite particles and gaps. The ceramic metal composite particles are in the millimeter range and the ceramic particles are bonded to the metal. The mixture matrix is bonded, with a porosity of less than 5 volume%, and the ceramic particle content is as high as 40 to 95 volume%, and the particle size and porosity are controlled by powder metallurgy.
A grinding ball with high ceramic particle concentration and low porosity is achieved, which significantly improves the wear resistance and mechanical properties of the grinding ball, reduces manufacturing costs, avoids defects and cracks, and extends the service life of the grinding ball.
Smart Images

Figure CN119183403A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite grinding ball, in particular a core-shell composite grinding ball obtained by conventional casting technology and having improved resistance to combined wear and impact stress. The grinding ball disclosed herein comprises a reinforced shell of a prefabricated ceramic body, which is composed of a composite shell (in particular two half shells) and has at least one inflow hole for cast metal. The shell comprises a three-dimensional interconnected network of aggregated ceramic-metal composite particles (granules) and gaps, the composite particles and gaps are all in the millimeter size range, wherein the ceramic microparticles (particles) are bonded in a binder metal matrix, and the millimeter-scale gaps are infiltrated and filled by the cast metal matrix. Background Art
[0002] The present invention relates to a wear-resistant composite grinding ball for use in a drum mill in the grinding industry, typically for clinker grinding in cement plants or ore grinding in mines. Grinding balls are often subject to high impact stresses and high wear due to abrasion or corrosion. Therefore, it is desirable that the grinding balls should exhibit high abrasion and corrosion wear resistance and a certain ductility in order to be able to withstand mechanical stresses, such as ball-to-ball or ball-to-liner impacts.
[0003] In view of the difficulty in matching these two properties with the same material composition, metal-ceramic composite grinding balls are proposed.
[0004] Document CN106914620A (2017) discloses a method for preparing a ceramic / metal composite grinding ball, which adopts selective laser cladding combined with three-dimensional digital modeling technology. The preform has a honeycomb structure and is placed in a mold cavity before casting.
[0005] Documents CN103357854 (2013) and CN113564511A (2021) disclose ceramic-reinforced grinding balls, wherein the reinforcing layer comprises embedded nano-scale ceramic particles on the surface and sub-surface of the grinding balls. The inner wall of the casting mold is coated with nano-ceramic particles.
[0006] Document CN104707972A (2015) discloses a composite grinding ball with a core-shell structure having a ceramic reinforcement embedded in a ferroalloy cast metal matrix. The document does not disclose the specific volume % of the ceramic bonded in the binder metal matrix, nor does it disclose the ceramic-metal composite particles, nor does it disclose a three-dimensional interconnected network of periodically alternating ceramic-metal composite particles and gaps, both of which are in the millimeter range.
[0007] Document CN109128098A (2019) discloses a method for manufacturing a ceramic-metal composite material, using Al2O3-ZrO2 powder to be transformed into a plurality of ceramic core blocks in a mold, wherein grinding balls are subsequently cast with manganese steel. The document discloses neither any ceramic particles bonded in a binder metal matrix nor an interconnected network of ceramic-metal composite particles of periodically alternating such bonded particles.
[0008] Document EP3885061 A1 (Magotteaux 2021) discloses a hierarchical composite wear-resistant part comprising a reinforcement of a three-dimensional interconnected network of periodically alternating millimeter-sized ceramic-metal composite particles and millimeter-sized gaps, wherein the millimeter-sized ceramic-metal composite particles have low porosity.
[0009] The grinding ball market is price sensitive, so the optimum level of wear resistance and price must be emphasized and manufacturing adjusted accordingly. The robustness of the ceramic preformed shell / hollow ball of aggregated ceramic metal particles during the casting operation and its ability to be penetrated by the cast metal without damage is critical to achieving this in an economical manner. Purpose of the Invention
[0010] The object of the present invention is to provide a ceramic reinforced core shell grinding ball made by conventional casting, which comprises a metal matrix of cast iron or steel and includes a reinforced shell structure of ceramic metal particles with low porosity, having a high concentration of micron-sized ceramic particles bonded in a metal binder matrix. Summary of the invention
[0011] The present invention discloses a composite grinding ball with a core-shell structure, wherein the shell of the core-shell structure comprises a ceramic reinforcement, and the ceramic reinforcement comprises: a three-dimensional interconnected network of periodically alternating ceramic-metal composite particles and interstices, the ceramic-metal composite particles and interstices having an average size in the millimeter range; The ceramic-metal composite particles comprise at least 40 volume %, preferably at least 60 volume %, and most preferably at least 70 volume % of ceramic particles, the ceramic particles being bonded in a binder metal matrix, the ceramic particles having an average size in the micrometer range; A three-dimensional interconnected network of ceramic-metal composite particles and interstices is embedded in a ferroalloy cast metal matrix, wherein the ferroalloy cast metal matrix fills interstices between the interconnected ceramic-metal composite particles of the three-dimensional interconnected network; The ceramic-metal composite particles embedded in the ferrous alloy cast metal matrix have a porosity of the following volume fraction: less than 5 volume%, preferably less than 3 volume%, most preferably less than 1 volume%, the porosity measurement is based on ISO 13383-2:2012 Annex A; The shell comprises the following volume content of ceramic-metal composite particles: at least 35 volume %, preferably at least 45 volume %; The ceramic reinforcement of the shell covers at least 85%, preferably 90%, most preferably 95% of the total surface of the grinding ball.
[0012] The present invention also discloses at least one or a suitable combination of the following structural features: - the ceramic particles are selected from carbides, nitrides, carbonitrides and borides or mixtures thereof; - ceramic particles are selected from titanium carbide, titanium carbonitride, tungsten carbide, niobium carbide, vanadium carbide, zirconium carbide, tantalum carbide, hafnium carbide and molybdenum carbide; - the thickness of the ceramic reinforced shell ranges from 2 to 15 mm, preferably from 2 to 10 mm, most preferably from 3 to 8 mm; The embedded ceramic-metal composite particles have a particle size distribution between 0.3 and 10 mm and an average particle size D between 1 and 4 mm, preferably between 1 and 3 mm. 50 , where the average particle size D can be measured by microscopic observation using a computer program and an optical microscope 50 , such that there are at least 250 ceramic-metal composite particles in a field of view of one or more polished cross-sections of the one or more samples, wherein a suitable threshold allows for subdivision of the particles in the grayscale image and the background; - The particle size of the bonded ceramic particles in the binder metal matrix is 0.1 to 50 μm, preferably 0.1 to 30 μm, and the average particle size D 50 0.5 to 20 μm, preferably 1 to 10 μm; - the binder metal matrix is selected from iron-manganese based alloys, iron-chromium based alloys and nickel based alloys; - The ferroalloy casting metal matrix comprises high chromium white cast iron (which comprises at least 11% by weight of chromium) or steel.
[0013] The present invention also discloses a method for manufacturing the composite grinding ball of the present invention, which comprises the following steps: a) providing or producing a ceramic-metal composite particle, the ceramic-metal composite particle comprising at least 40% by volume of micron-sized ceramic particles, the micron-sized ceramic particles being bonded in a binder metal matrix, the ceramic-metal composite particle having a porosity of less than 5% by volume, preferably less than 3% by volume, in particular less than 1% by volume; b) manufacturing a ceramic preform shell, preferably in the form of a half shell, which is a three-dimensional interconnected network of millimeter-sized ceramic-metal composite particles obtained in step a) and millimeter-sized gaps that are periodically alternating; c) assembling the shells obtained in step b) into a hollow sphere comprising one or two inflow openings and placing the hollow sphere in the cavity of a mold for the grinding balls to be cast; d) casting a metal matrix with an iron alloy, pouring the milled balls and simultaneously infiltrating the millimeter-scale interstices of the three-dimensional interconnected network of shells positioned according to step c); e) demoulding the composite grinding balls.
[0014] The present invention also discloses at least one of the following method features or their relevant combinations: - The manufacturing process of the ceramic-metal composite particles in step a) comprises: - grinding a powder composition comprising ceramic particles and a binder metal matrix in the presence of a solvent; - mixing 1 to 10%, preferably 1 to 6%, of wax into the powder composition; - Removal of the solvent by drying to obtain an agglomerated powder; - Pressing the agglomerated powder into strips, sheets or rods; - Crushing of strips, sheets or rods into particles in the millimeter size range; - Sintering the ceramic metal particles in a vacuum or inert atmosphere furnace at a temperature of 1200-1600° C. until a porosity of less than 5%, preferably less than 3%, even less than 1% by volume is reached. - a step of grinding the powder composition comprising ceramic particles and a binder metal matrix in the presence of a solvent until an average particle size D of 1 to 20 μm, preferably 1 to 10 μm, is obtained 50 The particle size of the powder is measured by laser diffraction using the MIE theory according to the guidelines given in ISO 13320:2020, where the refractive index and absorptivity are adapted to the ceramic particles, the obscuration is in the range of 10 to 15%, and the weighted residual is less than 1%. - The particle size of the sintered particles crushed from the strip, sheet or rod is 0.3 to 10 mm, preferably 0.4 to 6 mm, with an average particle size D 50 Selected from 1 to 6 mm, preferably 1 to 3 mm, the particle size is measured by dynamic image analysis according to ISO 13322-2:2006, or sieved according to ISO 4497:2020. - Step b) comprises the following steps: - mixing the ceramic-metal composite particles obtained according to the previous step with about 0.5 to 7 wt %, preferably 1 to 4 wt % of a binder (preferably an organic binder); - pouring the mixture into a shell mold and compacting; - drying the mixture at a suitable temperature and time in order to remove the solvent of the glue or to achieve curing by coagulation or catalyst; - De-molding the dried mixture and obtaining a shell of a three-dimensional interconnected network of periodically alternating millimeter-sized ceramic-metal composite particles and millimeter-sized gaps to assemble into a hollow preform positioned in a composite grinding ball mold. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A conventional grinding ball of the prior art produced by conventional casting using a high chromium iron alloy is shown.
[0016] Figure 2 Shown is a die for forming two half shells consisting of aggregated ceramic metal particles for reinforcing the outer shell structure of the grinding ball.
[0017] Figure 3 Shown in Figure 2 The two half shells of aggregated ceramic-metal particles pressed in a mold are assembled into a spherical preform with an inflow opening and placed in the cavity of a casting mold.
[0018] Figure 4 Details of aggregated ceramic-metal particles in the millimeter size range constituting a half shell of the aggregated ceramic-metal particles are shown.
[0019] Figure 5 Shown in Figure 2 The resulting reinforced hollow sphere (hollow spherical preform) of aggregated ceramic metal particles in the millimeter size range exhibits voids / inflow voids, allowing the casting metal to flow into the spherical mold to infiltrate the three-dimensional ceramic metal shell structure, thereby filling the gaps between the ceramic metal fine particles.
[0020] Figure 6 Presented with Figure 5 Similar structure. Ceramic metal particle reinforced hollow spheres have two inflow holes that allow the cast metal to pass through the hollow spheres when additional grinding balls are cast in the same branch of the mold (see Fig. 9 , in which the grinding balls are cast in clusters).
[0021] Figure 7 The present invention shows that before casting in cluster structure Figure 6 The reinforced hollow ball with two inflow holes is placed in the cavity of the sand mold (see Fig. 9 ).
[0022] Figure 8 The fabrication and assembly of the sand mould and the positioning of the reinforcing hollow spheres in the cavity of the created sand mould are schematically presented.
[0023] Fig. 9 The construction of a mold for cluster-cast grinding balls is presented schematically.
[0024] Fig.10 is a cross-sectional view of a cast grinding ball according to the present invention showing the reinforcements in the grinding ball shell.
[0025] Fig.11 Detailed view of a polished cross section of a portion of an 80 mm grinding ball showing details of the ceramic metal grains surrounded by cast metal.
[0026] Fig.12 The microscopic TiC particles bonded in the binder metal matrix are shown. Figure 4 A high magnification image of a portion of a single ceramic-metal composite particle is shown in FIG.
[0027] Fig.13 is a schematic diagram of the inventive concept based on the size differences between bonded ceramic microparticles (grains) in a metal binder matrix to form millimeter-sized particles of a ceramic-metal composite material integrated in a three-dimensional network in the reinforcement of a wear-resistant part.
[0028] Fig.14 A cross section of a sample containing particles in a reinforcement shell is presented, in which the average particle size D of the ceramic metal particles is obtained. 50 This cross section is used in the method of
[0029] Fig.15 Schematic diagram of the method for measuring Feret diameter, which is used to obtain the average particle size D of ceramic metal particles. 50 method (described below). DESCRIPTION OF THE PREFERRED EMBODIMENTS OF THE INVENTION
[0030] The present invention relates to a metal matrix composite grinding ball, in particular to a ceramic reinforced grinding ball produced by conventional casting. The metal matrix composite grinding ball is composed of a metal core surrounded by a reinforced shell structure, wherein the reinforced shell structure comprises dense irregular ceramic metal composite particles alternating with millimeter-scale average gaps, wherein the porosity of the ceramic metal composite particles is less than 5% by volume, preferably less than 3% by volume or 2% by volume, more preferably less than 1% by volume, and the particle size distribution is about 0.3 to 10 mm, preferably 0.8 to 6 mm, and the average particle size is 1 to 4 mm, preferably 1 to 3 mm, and the gap is 0.5 to 4 mm, preferably 1 to 3 mm.
[0031] The ceramic-metal composite particles consist of ceramic particles, in particular boride, nitride or carbide particles, such as TiC, TiCN, NbC, TaC, WC, preferably titanium carbide, titanium nitride or titanium carbonitride, bound in a metal binder matrix.
[0032] For wear applications, ceramic particles provide high wear resistance, while metals improve toughness in particular. Depending on their specific use (requiring impact resistance, abrasion resistance or corrosion resistance), the ceramic-metal composite particles of the reinforced grinding balls of the present disclosure comprise different proportions of micron-sized ceramic particles (40 to 95 volume %, preferably 60 to 90 volume %, more preferably 70 to 90 volume %, of the particles, with a size of about 0.1 to 50 μm, preferably 0.5 to 20 μm, more preferably 1 to 10 μm) bonded in a metal binder phase, which may be, for example, Fe-based, Ni-based or Mo-based.
[0033] The hollow prefabricated ceramic metal shell structure / hollow ball is placed in the mold cavity, and then the iron alloy (preferably chromium cast iron or steel) is poured into the grinding ball mold (cluster mold) and penetrates the gaps of the outer ceramic metal shell structure surrounding the grinding ball core. The millimeter-sized ceramic metal fine particles are then completely embedded in the cast metal matrix (see Fig.10 and 11 ). The thickness of the prefabricated shell is variable and can be selected between about 2 and 15 mm, preferably between 2 and 10 mm, most preferably between 3 and 8 mm.
[0034] The following table shows the theoretically possible reinforcement ratios, taking into account the grinding ball diameter and the reinforcement shell thickness. Grinding balls from 10 to 125 mm have been commercialized for various applications, but the most common diameters are shown below. For a grinding ball with a nominal diameter of 80 mm and a reinforcement shell thickness of only 5 mm, the proportion of reinforcement volume is already an astonishing 33% by volume of the ball volume.
[0035] In the present invention, expressions such as TiC, TiCN, TiN, WC, WB, etc. should not be understood in a strict stoichiometric chemical sense, but should be understood as carbides, nitrides, borides, etc. according to their crystal structures. For example, titanium carbide has a wide composition range, in which the C / Ti stoichiometric ratio varies from 0.47 to 1, and preferably the C / Ti stoichiometric ratio is higher than 0.8, higher than 0.9 or even better. For example, titanium carbonitride is sometimes expressed as TiCN or Ti2CN, or even Ti(C,N)…
[0036] The volume content of the ceramic-metal composite particles in the ceramic structure constituting the outer reinforcement shell of the grinding balls (excluding hollow portions such as inflow holes or recesses, if any) is typically between 35 and 70 volume %, preferably between 40 and 65 volume %, most preferably between 45 and 60 volume %, depending on their specific use, resulting in an average ceramic particle concentration in the reinforcement volume of between 14 and 67 volume %, preferably between 24 and 59 volume %, more preferably between 30 and 54 volume %.
[0037] The table below shows the volume % of the ceramic particle content, taking into account the ceramic weight and volume % in the millimeter-sized particles and the bulk density of the particles.
[0038] The reinforcing outer part of the grinding ball is made of an aggregate of irregular millimeter-sized ceramic-metal composite particles, with a particle size distribution of about 0.3 to 10 mm, preferably 0.5 to 6 mm, more preferably 0.8 to 4 mm. The average particle size is preferably selected between 1 and 6 mm, more preferably between 1 and 3 mm, for example 2 mm, depending on the desired shell thickness. See Figure 4 The particle size distribution is essentially free of particles smaller than 0.3 mm, and the proportion of particles smaller than 0.5 mm is less than 5% to maintain sufficient interstices to be infiltrated and filled by the casting metal. The appropriate particle size distribution can be obtained by sieving the particles and can be customized according to the desired bulk density shown in the table above.
[0039] The ceramic-metal composite particles are typically assembled into two half shells (although other assembly configurations are possible) using a binder (an inorganic glue, such as the well-known sodium or potassium silicate glass glues; or an organic glue, such as a two-component glue resulting in polyurethane or phenolic resins). These shells form an open structure of a three-dimensional interconnected network of agglomerated / aggregated ceramic-metal composite particles bound by the binder, wherein the packing of the particles leaves open gaps between the particles that can be filled by the liquid casting metal (see Figure 3 ). Combine the two half shells 2×2 to form a hollow sphere (see Figure 5 ) and placed in a mold (see Figure 7 ), and then pouring the iron alloy to form a ceramic reinforced grinding ball. The assembly of the shell can be a mortise and tenon assembly or any other suitable assembly, allowing good performance during the pouring of the cast metal. The connection between the shell parts is usually the weak point of the preform, and it is preferred to place them vertically or at least not parallel to the parting line of the mold to avoid an increase in defects (the mold parting line is already a weak point for traditional grinding balls).
[0040] Liquid metal is then poured into the grinding ball mold, the liquid metal filling the open gaps between the ceramic metal particles. Millimeter-scale gaps are to be understood as gaps with an average size of 0.5 to 4 mm, preferably 1 to 3 mm, depending on the compactness of the ceramic reinforcement and the size of the particles. The size of the ceramic metal composite particles is selected according to the thickness of the reinforcement shell for reasons of mechanical resistance and permeability. A shell thickness of 3 mm can be achieved using ceramic metal particles with an average size of about 1 to 2 mm, while a shell of 10 mm thickness can be achieved using ceramic metal particles with an average size of 3 to 6 mm.
[0041] Ceramic-metal composite particles are usually manufactured by powder metallurgy, where a blend of ceramic and metal powders with appropriate size distribution is formed and then liquid-phase sintered.
[0042] Typically, the powder has a diameter of 0.1-50 μm and contains ceramic particles as the main component and 5 to 60% of a metal binder, which can be a powder of the individual components or an already alloyed powder. The powders are first mixed and / or ground in a ball mill (depending on the initial powder size), dry or wet (for example with alcohols such as isopropanol to avoid oxidation of the metal powder). Some organic additives may be added for dispersion or shaping purposes. In the case of wet grinding, a drying step may be required. This can be carried out by any suitable technique, for example by vacuum drying or spray drying. Shaping to form strips, rods, blocks or sheets is usually carried out by: cold uniaxial, isostatic roller press or injection molding or any other shaping method.
[0043] For example, the strip or sheet can be easily broken into fine particles (grains) and can be screened. It can be advantageous to achieve irregular particle shapes without easy pull-out directions (the particles are well mechanically retained in the cast metal) or round particles (the particles are well metallurgically retained in the cast metal). The pressed, extruded or crushed particles are then sintered at a suitable temperature, preferably under vacuum, inert gas or a combination thereof. During liquid phase sintering, driven by capillary forces, particle rearrangement occurs, thereby reducing porosity. Crushing can also be performed after the sintering step.
[0044] The cast iron alloy that embeds the ceramic-metal composite particles and fills the gaps of the grinding ball shell is preferably an iron alloy (chrome white iron, steel, manganese steel, . . . ). Advantages
[0045] The invention allows obtaining very high ceramic particle concentrations (up to 95% by volume) in ceramic-metal composite particles by conventional casting, with a low risk of defects inside the cast structure (porosity, cracks, inhomogeneities...).
[0046] In the present invention, a good average concentration of ceramic can be achieved in the volume of the reinforced shell of the grinding ball by the low porosity of the ceramic-metal composite particles. Depending on the compaction / packing and the proportion of micron-sized ceramic particles in the ceramic-metal composite particles in the grinding ball shell, values of up to about 67% by volume of ceramic can be achieved.
[0047] The grinding balls of the present invention are substantially free of pores and cracks, resulting in better mechanical properties and wear resistance.
[0048] The size of the ceramic particles and ceramic metal composite particles (ceramic particles + metal binder) of the present invention can be widely controlled during the manufacturing process (selection of raw materials, grinding, screening, molding process and sintering conditions). The use of sintered millimeter-scale ceramic metal composite particles made by powder metallurgy allows control of fine particle size and porosity, the use of metal alloys of various compositions as binder metal matrices, high concentrations of ceramics are easy to mold inserts without requiring a lot of labor, and even under high thermal shock conditions, good fine particle internal health after casting. Manufacturing of ceramic-metal composite particles:
[0049] As described above, the ceramic powder (40 to 95% by volume, preferably 60 to 90% by volume, more preferably 70 to 90% by volume) and the metal powder (5 to 60% by volume, preferably 10 to 40% by volume, more preferably 10 to 30% by volume) as the binder metal matrix are ground and / or mixed in a ball mill using a liquid, which can be, for example, water or alcohol, depending on the sensitivity of the metal binder to oxidation. Various additives (antioxidants, dispersants, binders, plasticizers, lubricants, pressing waxes) can also be added before or after drying for various purposes.
[0050] Once the desired average particle size D is reached 50 The slurry is dried (for example, by vacuum drying or spray drying) to obtain powder agglomerates containing the above-mentioned organic additives.
[0051] The agglomerated powder is fed to a roller granulation device through a hopper. The machine contains two pressure rollers through which the powder passes and is compacted. At the outlet, a continuous strip (sheet) of pressed material is obtained, which is then broken to obtain ceramic-metal composite particles. These particles are then screened to the desired size. Unwanted particle size fractions are recovered as needed. The resulting particles typically have a relative density of 40% to 70% (depending on the level of compaction, powder properties and blend composition).
[0052] The size distribution of the particles can also be adjusted according to the crushing method and their shape can be adjusted to a cubic or flat shape (impact crushing will provide more cubic particles, while compression crushing will produce more flat particles) or a rounded shape, for example by rolling the particles in a drum or belt for a sufficiently long time or extending the screening time or step. Round particles are particularly beneficial for reducing stress concentrations in the shell (compared to angular particles). The particles obtained generally have a size that, after sintering, will provide particles of about 0.5 to 10 mm, preferably 0.8 to 6 mm, more preferably 1 to 4 mm, and even more preferably 1 to 3 mm. The particles can also be obtained by directly making fine particles or making significantly larger parts by classical uniaxial pressing or granulation of the powder blend, which are then further broken into particles before or after sintering.
[0053] Finally, liquid phase sintering can be carried out in a furnace at a temperature of 1200-1600°C for a few minutes or hours, under vacuum, N2, Ar, H2 or mixtures thereof, depending on the metal phase (type and amount of binder) and the type of ceramic particles (carbide, nitride, carbonitride, boride...) until the desired porosity is reached, preferably below 5% by volume, more preferably below 3% by volume, most preferably below 2% by volume, or even below 1% by volume. Example of realization of a ceramic preform shell structure
[0054] As described above, the ceramic-metal composite particles are agglomerated with the aid of a binder or by confining the particles in a mold or by any other means. The proportion of binder relative to the total weight of the particles does not exceed 10% by weight and is preferably between 0.5 and 7% by weight. The binder may be inorganic or organic. A binder based on sodium silicate or potassium silicate or a two-component binder resulting in polyurethane or phenolic resin may be used.
[0055] The low porosity ceramic-metal composite particles are mixed with a binder and placed in a mold to form, for example, two half shells (see Figure 2 After the glue has solidified (for example, after evaporation of water in an inorganic silicate glue at 100° C., for a polyurethane-based glue, the glue solidification can also be obtained by, for example, aeration with CO2 or amine gas or by adding a catalyst to the glue mixture to achieve hardening over time), the two half shells are hardened and can be demoulded (see Figure 3 ), and then assembled into a hollow spherical structure with at least one inflow hole (see Figure 4The interconnected network structure of the ceramic metal particles comprises 35 to 70 vol. %, most preferably 55 vol. %, of dense ceramic metal particles and 65 to 30 vol. %, more preferably 45 vol. % of voids (millimeter gaps) in the 3D interconnected network, depending on the particle shape, size distribution, glue content, vibration during particle positioning or tapping of the particle bed when making the shell. Casting of grinding balls in cluster moulds
[0056] Grinding balls are usually cast in a multi-mold configuration, also known as a "cluster mold." In such a mold, up to 40 40 mm grinding balls and up to 16 100 mm grinding balls can usually be cast in one casting operation. Fig. 9 It is also possible to cast grinding balls of different sizes together in the same cluster mould.
[0057] The half shells of the assembled ceramic-metal particle structure form a hollow sphere (hollow spherical prefabricated structure) and contain one or two openings (inflow holes) for introducing liquid casting metal and are positioned in the cavity of a conventional sand mold or metal shell mold. The hot liquid iron alloy (preferably chrome white iron or steel) is then poured into the milled ball cluster mold.
[0058] Thus, the hot liquid ferroalloy penetrates and fills the millimeter-sized gaps between the ceramic metal particles reinforcing the shell structure. If an organic binder is used, the casting alloy partially melts the metal binder matrix surface on the particle surface, or the interdiffusion of elements between the two alloys causes an extremely strong bond between the particles and the casting ferroalloy matrix.
[0059] The sand mold is then removed and the grinding balls cleaned of residual sand and conventional process steps for finishing the casting known to those skilled in the art can be followed (knockout, shot peening, grinding, additional heat treatments such as annealing, quenching, tempering, ...). Measurement method
[0060] To measure porosity, grain or particle size, prepare samples for metallographic examination that are free from grinding and polishing marks. Care must be taken to avoid tearing off particles, as this can lead to a misleading assessment of porosity. Guidelines for specimen preparation can be found in ISO 4499-1:2020 and ISO 4499-3:2016, 8.1 and 8.2. Porosity determination:
[0061] From the measured density and the theoretical density of the free particles before casting, the volume fraction of the porosity of the free particles can be calculated.
[0062] The measurement of the porosity volume fraction of particles embedded in a metal matrix is based on Annex 2 of ISO 13383-2:2012. Although this standard is dedicated to fine ceramics, the method described for measuring the porosity volume fraction can also be used for other materials. Since the samples here are not pure fine ceramics but hard metal composites, the sample preparation should be carried out according to ISO 4499-1:2020 and ISO 4499-3:2016, 8.1 and 8.2. Etching is not necessary for the porosity measurement, but it can be performed as it does not change the measurement results. Average ceramic particle size D 50 :
[0063] The average particle size of bonded ceramic particles is calculated by the linear intercept method according to ISO 4499-3:2016. Five images of the microstructure of five different particles are taken at known magnifications using an optical or electron microscope so that there are 10 to 20 ceramic particles across the field of view. Four linear intercept lines are drawn across each calibration image so that a single particle is not spanned by a line more than once.
[0064] When the line intersects the ceramic particle, the length of the line (l i ) (where i=1, 2, 3, ..., n represents the 1st, 2nd, 3rd, ..., nth fine particle). Incomplete particles touching the edge of the image must be ignored. At least 200 particles must be counted.
[0065] The average linear intercept particle size is defined as: Average particle size of ceramic metal particles D 50 Measurement
[0066] One or more micrographs of a polished cross section of the sample are made using a computer program and an optical microscope (e.g. a general image field obtained with an Alicona Infinite Focus). Together, these micrographs contain at least 250 different ceramic-metal particles. Appropriate thresholding allows the subdivision of the grayscale image into features of interest (particles) and background (see Fig.11 ). If the thresholds were inconsistent due to poor image quality, a manual phase was used which involved hand-drawing the grain, scale bar (if present), and image boundaries on tracing paper and then scanning the tracing paper.
[0067] The Feret diameter is the distance between two tangent lines placed perpendicular to the measurement direction and is measured for each particle in all directions by image analysis software (e.g. ImageJ). Fig.15 Give an example.
[0068] Determine the minimum Feret diameter for each particle in the image. The minimum Feret diameter is the shortest Feret diameter in the measured set of Feret diameters. At least 250 different particles must be measured. Particles that touch the edge of the image must be ignored. The value of the minimum Feret diameter for each particle is taken as the equivalent diameter x. The volume size distribution q3(x) of the particles is then calculated based on a sphere of diameter x. According to ISO 9276-2:2014, the D 50 Should be understood as the volume weighted average size The average particle size D of the ceramic-metal composite particles during particle production 50 Measurement
[0069] Particle size can be measured by dynamic image analysis according to ISO 13322-2:2006 using a Camsizer from Retsch or equivalent. The particle diameter used for size distribution is Xc min , which is the shortest chord measured in the maximum set of chords of the particle projection (for results close to screening / sieving).
[0070] Particle size D 50 Based on Xc min The volume weighted average size of the volume distribution of particles. The average particle size and distribution of particles can also be measured by sieving according to ISO 4497:2020. Particle size measurement of powders during grinding:
[0071] The particle size of the powder during grinding is measured by laser diffraction and MIE theory using Malvern's Mastersizer 2000 according to the guidelines given in ISO 13320:2020. The refractive index and absorptivity should be set according to the material being measured. For example, the refractive index of TiC is set to 3 and the absorptivity is set to 1. The obscuration must be in the range of 10% to 15% and the weighted residual must be less than 1%. Example In fields of application where corrosion resistance, abrasion resistance or impact resistance are required, grinding balls are usually subjected to various stresses. Grinding balls are therefore provided for their specific use in the presence of one or more of the above-mentioned wear mechanisms. However, grinding balls are not only tailored to the material to be ground, but also to the specific grinding machine where diameter, lining and volume filling play an important role. Therefore, the performance comparison of the grinding balls of the invention with the grinding balls of the prior art must be carried out in a specific grinding environment and in the specific context of the expected results in terms of corrosion resistance, abrasion resistance or impact resistance. Example of a grinding ball tested in practice in an industrial grinding machine This example is intended to illustrate the present disclosure but should not be considered limiting.
[0072] Preparation of ceramic-metal composite particles For the four different types of ceramic-metal composite particles 1 to 4, the following raw material powders were used, all of which had a particle size of less than 44 μm. TiC, TiC 0.5 N 0.5 , WC, NbC, Mo2C, iron, manganese, chromium, and nickel. Table 1
[0073] The composition of ceramic-metal composite particle 1 is particularly suitable for impact resistance because it has a relatively low content of ceramic particles (45 wt. % TiC) bonded in a tough manganese steel binder matrix.
[0074] The composition of ceramic metal composite particles 2 and 3 is particularly suitable for wear resistance because it has a high content of ceramic particles (85 wt. % TiC) bonded in a hard high chromium white cast iron wear resistant binder matrix.
[0075] The composition of the ceramic-metal composite particle 4 is particularly suitable for corrosion and wear resistance because it has a high content of a complex mixture of ceramic particles (TiC 0.5 N 0.5 + WC + NbC + Mo2C = 85 wt% in total), finely tuned to be bonded in a corrosion resistant nickel binder. Other ceramic particles can be added to create complex solid solution particles, controlling or fine tuning the grain size, morphology and / or core-edge structure of the hard ceramic particles.
[0076] The powder according to the composition of Table 1 was mixed with isopropanol and metal grinding balls in a ball mill and ground for 24 hours to achieve an average particle size D of about 3 μm. 50 .
[0077] Organic wax binder (powder form, 2 wt %) is added and mixed with the obtained powder. Alcohol is removed by a vacuum dryer with a rotating blade (the alcohol is condensed for reuse). The agglomerated powder obtained is then sieved through a 500 μm sieve. By compacting between the rotating rollers of a roller granulator, a band with 60% theoretical density of a ceramic / metal powder mixture is manufactured. Then by forcing the band to pass through a sieve with a suitable mesh size, it is broken into irregular particles. After the crushing, the particles are sieved to obtain the required particle size distribution. These irregular porous particles are subsequently sintered at high temperatures (typical temperature-time pairing is, for example, 1430 ℃ for 2 hours) in a high vacuum furnace with a low argon partial pressure, until minimum porosity (<5 volume %) is reached, preferably less than 3 volume %, even less than 1 volume %, if necessary.
[0078] The low porosity (<5% by volume) sintered particles are then mixed with about 1% by weight of a two-component polyurethane glue (e.g., a mixture of 50% by weight AVECURE 335F PART 1—aromatic hydrocarbons, phenol, 2-butoxyethyl acetate and 50% by weight AVECURE 635F PART 2—diphenylmethane diisocyanate from ASK chemicals) and poured into a silicone or plastic mold of the desired shape (vibration or pressure may be applied to facilitate filling and packing of the mold to ensure that all particles are properly packed) (see Figure 2 The polyurethane is then hardened using ethyldimethylamine gas (e.g. AVECURE 3D from ASK Chemicals) as a catalyst and once the shell is hard enough it can be demoulded. Such an operation can be easily automated on core shooting machines widely used in casting operations.
[0079] like Figure 5 and Figure 6 As shown, these shells contain about 55% by volume of dense ceramic-metal composite particles (the voids / mm gaps between particles are about 45% by volume). Each preformed hollow sphere ceramic-metal particle structure is positioned in the cavity of a milled ball cluster mold (see Figure 7 Then, hot liquid high chromium white cast iron with a suitable composition is poured into the mold according to the test conditions (Alloy 1, Alloy 2 or Alloy 3). The hot liquid high chromium white cast iron fills the millimeter-scale gaps between the particles of the grinding ball reinforcement shell. Casting alloy for casting the grinding balls of Examples 1 to 4 weight% C Cr other Fe Casting Alloy 1 2.2 16.5 <2 margin Casting Alloy 2 2.85 14.5 <2 margin Casting Alloy 3 2.3 29 <2 margin Example 1 (Alloy 1+Particle Composition 1)
[0080] Alloy 1 contains 2.2 wt% C and 16.5 wt% Cr, which is particularly suitable for impact conditions, and has appropriate heat treatment to improve impact resistance. The particles of composition 1 were used to make the shell. The composite grinding balls and reference metal grinding balls were placed together in the same ball mill to process the same platinum ore for the same period of time under significant impact conditions for comparison. Examples 2 and 3 (Alloy 2 + Particle Compositions 2 and 3)
[0081] Alloy 2 contains 2.85 wt% C and 14.5 wt% Cr, which is particularly suitable for abrasive conditions, and has appropriate heat treatment to improve wear resistance. Shells were made using particles of composition 2 and composition 3. Composite balls were compared to reference metal balls in the same ball mill under significant abrasive conditions using copper ore. Example 4 (Alloy 3 + Particle Composition 4)
[0082] Alloy 3 contains 2.3 wt% C and 29 wt% Cr and is particularly suitable for highly corrosive conditions. Particles of composition 4 were used to make the shell. Composite balls were compared to reference metal balls in the same ball mill under significantly corrosive conditions using magnetite iron ore.
[0083] As for other elements, it is understood that alloys 1, 2 and 3 also contain <2 wt. % of other common alloying elements (Si, Mn, Mo, Ni...) known to those skilled in the art, depending on the specific properties and targeted heat treatment.
[0084] After casting, the shell is 47 to 58% by volume of ceramic metal particles, of which about 57% to 89% by volume are high concentrations of micron-sized ceramic particles (e.g., titanium carbide, titanium carbonitride, niobium carbide, tungsten carbide ... and / or mixtures / combinations) bonded in their binder metal matrix. The total volume content of ceramic particles in the reinforcement shell after casting the grinding balls in Examples 1 to 4 varies from about 27 to 52% by volume, but even higher values can be reached.
[0085] All the variables needed to calculate each relevant parameter are shown in the table below. The word "particles" in the table refers to ceramic-metal composite particles. The density and porosity of these particles are interdependent. Summary of technical parameters of the grinding balls of various examples tested. Related parameters Example 1 Example 2 Example 3 Example 4 Ball diameter(mm) 80 90 90 70 Shell thickness(mm) 5 8 8 3 Average particle size (mm) 2 3 3 1 Particle porosity (%) 0.20% 2.50% 0.50% 0.50% Weight of particles in shell (g) 251 489 499 126 <![CDATA[Particle density (g / cm 3 )]]> 6.19 5.07 5.18 6.12 <![CDATA[Volume of the enhanced part (cm 3 )]]> 86.4 166.2 166.2 41.1 Ratio of reinforcement volume / ball volume 32% 44% 44% 23% Ratio of reinforcement surface to ball surface 98% 98% 98% 97% Volume ratio of particles in shell 47% 58% 58% 50% <![CDATA[Volume of the particles in the shell (cm 3 )]]> 40.6 96.4 96.4 20.5 Final ceramic particle content in granules (volume %) 57% 87% 89% 88% Final ceramic particle content in shell (volume %) 27% 51% 52% 44% Calculated performance indicators compared with conventional grinding balls
[0086] An overview of grinding media testing is given in the article "Overview of grinding media consumption incomminution" (Slabbert, Paton, Moema and Zimba) presented at the World Gold Congress.
[0087] Practical testing of grinding balls on industrial grinding machines is particularly difficult to manage due to the low proportion of test grinding balls relative to the loading of conventional grinding balls. Since the grinding machine contains grinding balls in different stages of wear and with a large diameter size distribution (e.g., 10 to 70 mm in diameter), the test sample usually accounts for less than 0.1% (400 balls out of 400,000 to 800,000 balls). The main difficulty here is that after several days or weeks of grinding, at least a significant number of composite and reference balls need to be found among thousands of conventional grinding balls in order to be able to measure a representative average weight loss percentage of the composite test balls for comparison with the reference metal grinding balls.
[0088] A way to solve this problem is to use grinding balls that are slightly larger in diameter (about 10 mm larger) than those that are regularly added and already present in the conventional grinder. For example, if the diameter of the fresh conventional grinding balls regularly added to the industrial grinder is 60 mm, the diameter of the test grinding balls (composite grinding balls and reference grinding balls) is selected to be 70 mm in diameter in order to more easily retrieve the marked balls. Since these balls are larger, they are not only easier to find visually, but they also have a natural tendency to "float" on the surface of the conventional grinding load.
[0089] The evaluation of the wear performance of the disclosed grinding balls was carried out in the actual case of grinding of copper ore, magnetite iron ore and platinum ore in 3 industrial mills A, B, C (having the following characteristics and conditions):
[0090] The copper ore was ground in the presence of the grinding balls of Example 2 and then tested with the grinding balls of Example 3 (diameter 90mm in all) - Mill A with a diameter of 7.31 m and a length of 10.97 m, - Contains 660 tons of conventional grinding balls (33% volume filling) - Several tons of conventional grinding balls with a diameter of 76 mm are added regularly every day to compensate for wear -Speed is 11.9 rpm - Traction power is 10500kW -Processing 950 tons of copper ore per hour -use Abrasion condition -Test duration: 8 days
[0091] Grinding of magnetite iron ore in the presence of grinding balls (70 mm) of Example 4 - Mill B with a diameter of 4.6 m and a length of 6.7 m, -Filled with 165 tons of conventional grinding balls (35% volume fill) - Several tons of conventional grinding balls with a diameter of 60 mm are added regularly every day to compensate for wear -Speed 15.1rpm - Traction power is 2300kW -Processing 420 tons of magnetite iron ore per hour -use corrosion condition -Test duration: 20 days
[0092] Grinding of platinum ore in the presence of grinding balls (80 mm) of Example 1 - Mill C with a diameter of 7.925 m and a length of 11.735 m, -Filled with 800 tons of conventional grinding balls (32% volume filling) - Several tons of conventional grinding balls with a diameter of 70 mm are added regularly every day to compensate for wear - Speed between 10.5 and 11.5 rpm - Traction power is 15000kW -Processing 1,000 tons of platinum ore per hour -use Shock condition -Test duration: 10 days Preparation of test samples
[0093] For the performance testing of the composite grinding balls of Examples 1 to 4, and for the metal reference ball type, 200 grinding balls were produced for each example, and each grinding ball of the same alloy and reinforcement was marked with the same identification means (e.g., all grinding balls of Example 1 had one or two holes of defined diameter and position; all grinding balls of Example 2 had 2 holes of different diameters and positions, etc.). All grinding balls of the same composition were further processed or ground to have the same weight (+ / -2Kg for grinding balls of 80mm diameter) with a tolerance of + / -5 grams, preferably + / -2 grams. The composite grinding balls of the present disclosure and the reference metal grinding balls were made of the same iron alloy and subjected to the same heat treatment so that the effect of the reinforcement could be evaluated as the only variable.
[0094] In the next step, 200 composite test grinding balls were loaded into an industrial mill together with 200 reference metal grinding balls (the composite balls of Example 1 were loaded into Mill C, the composite balls of Examples 2 and 3 were loaded into Mill A, and the composite balls of Example 4 were loaded into Mill B). The composite balls of Example 2 and Example 3 were tested separately (one after another) in Mill A, each time using 200 reference metal grinding balls.
[0095] The above industrial mills already contained their usual conventional grinding ball loads with a filling rate of about 35% by volume. This means that there are 660 tons of conventional grinding balls for Mill A, 165 tons for Mill B and 800 tons for Mill C, while the number of composite and reference grinding balls (200 composite grinding balls and 200 reference balls in each mill) is only 600 to 900 kg, so the effect on the grinding capacity is negligible. Therefore, the addition of the test grinding balls (composite grinding balls and reference grinding balls) has no significant effect on the overall mill filling.
[0096] The mill then needs to be run for a sufficiently long period of time to observe sufficient wear that can be measured. Under 24 hour / day conditions, the required period of time is typically on the order of several days or weeks.
[0097] Depending on the type of ore to be ground, the wear of conventional grinding balls for magnetite iron ore is known to be about 0.5 mm / 100 hours in diameter (about 2.4 mm after 20 days), while for copper ore, about 1.5 mm / 100 hours in diameter is observed (about 3 mm after 8 days). For platinum ore, the wear is expected to be about 1.3 mm / 100 hours (about 3 mm after 10 days). Considering this indicator related to the wear rate of conventional grinding balls, the test duration was chosen to ensure that the wear is maintained within the thickness of the reinforcing shell, so as to properly interpret the effect of the reinforcing shell itself.
[0098] Finally, the mill was stopped and the found and identified test grinding balls (usually less than 10% of the starting number) were weighed to evaluate the average mass loss and calculate the performance index, as shown in the results table below. Performance index calculation
[0099] For each example of grinding balls, the average weight loss was measured before and after the test duration, and the average weight loss percentage was calculated. Weight loss percentage = (initial weight - final weight) / initial weight The performance index is defined as follows: Reference weight loss is the average weight loss of the reference metal grinding balls. PI = Average weight loss of the reference metal grinding balls / Average weight loss of the test composite grinding balls
[0100] A performance index above 1 means that the test composite grinding ball of the invention has less wear than the reference, and below 1 means that the test composite grinding ball has more wear than the reference. The reference grinding ball is a conventional grinding ball made of the same cast alloy but without any ceramic reinforcement. As shown in the table below, the grinding balls of the present invention show better performance on average due to the reinforced shell. Example Particle composition Casting alloy composition Performance Indicators 1 1 1 2.3 2 2 2 2.7 3 3 2 4 4 4 3 3.1
[0101] The performance of the composite grinding balls disclosed herein is compared to the conventional grinding balls described above. As long as the reinforcement shell is not completely worn and completely lost, the thickness of the reinforcement shell naturally has an impact on the overall performance of the grinding balls. A grinding ball with a composite reinforcement shell thickness of 10 mm will have better long-term performance than a grinding ball with a reinforcement shell thickness of 5 mm. Impact of performance indicators on overall grinding performance
[0102] The following table compares the wear (expressed as average weight loss percentage) of Examples 1 to 4 (composite grinding balls) with their respective reference grinding balls. The increased life was calculated taking into account their performance indicators and their influence on the life of the grinding balls.
[0103] The life of the grinding balls is usually evaluated by the time required for the grinding balls to wear from their initial diameter to 20 mm. Once the diameter of the grinding balls reaches 20 mm, they are considered small enough to leave the mill through the outlet trunnion together with the ground material. The measured weight loss is converted into a diameter reduction per unit time, and the increased life span can be calculated.
[0104] Due to the reinforced shell structure, a significant lifetime increase is observed, allowing the diameter of the grinding balls to remain close to their initial value for a longer period of time.
[0105] Examples 1 to 4 show significantly better performance of composite core-shell grinding balls with different particle compositions and properties, casting alloys, and testing conditions. Example 3 shows that the composite shell performs best when the particle has no significant porosity. The performance indicators of Example 2 show the impact of higher porosity in the particle. Advantages of the present invention
[0106] Compared with conventional grinding balls, the present invention has the following advantages: Better wear efficiency due to better wear resistance of the cover layer which occupies most of the wearable volume (having reinforcement everywhere in the ball is futile) The composite grinding balls can be provided with improved wear resistance and / or mechanical properties by adjusting the nature, size and volume content of the ceramic particles and using an appropriate metal binder matrix for the ceramic-metal composite particles, such as combining a high mechanical properties manganese steel with an appropriate iron casting alloy (e.g., high chromium white cast iron for wear resistant parts), wherein the binder metal matrix may be different and complementary to the cast iron alloy metal matrix. Better wear resistance and / or mechanical properties of the grinding balls due to controlled porosity and / or crack defects in the particles before casting. Easy / simple process Terms The metal-ceramic composite grinding ball of the present disclosure can also be described as:
[0107] A metal matrix composite grinding ball having a ceramic reinforced shell structure of millimeter-sized ceramic metal grains, the millimeter-sized ceramic metal grains having a porosity of less than 5%, preferably less than 3% by volume, and most preferably less than 1% by volume. The millimeter-sized grains contain a concentration of ceramic particles bonded in a binder metal matrix greater than 40%, the thickness of the reinforced shell is between 2 and 20 mm, preferably 3 to 15 mm, more preferably 4 to 12 mm, and the reinforced volume accounts for more than 10% by volume of the total volume of the grinding ball, preferably more than 15%.
[0108] A metal matrix composite grinding ball having a core-shell structure, the shell comprising a ceramic reinforcement, the ceramic reinforcement comprising an interconnected network of ceramic-metal composite particles with interstices and one or two substantially rounded surfaces free of ceramic reinforcement, the rounded surfaces accounting for less than 10% of the total surface of the shell, the ceramic-metal composite particles presenting an average size D of 2 to 5 mm, preferably 2 to 3 mm 50 , and the gap presents an average size D of 0.5 to 3 mm 50 ; The ceramic-metal composite particles comprise at least 40 volume %, preferably at least 65 volume %, and most preferably at least 85 volume % of ceramic particles bonded in a binder metal matrix, the ceramic particles having an average size D of 2 to 5 μm. 50 ; The ceramic-metal composite particles have a porosity volume fraction of less than 5 vol%, preferably less than 3 vol%, most preferably less than 1 vol%, as measured in accordance with ISO 13383-2:2012; The network of composite particles and interstices is embedded in a ferroalloy cast metal matrix, wherein the ferroalloy cast metal matrix infiltrates and fills the interstices between the interconnected composite particles in the three-dimensional network; The shell comprises a ceramic reinforcement comprising ceramic-metal composite particles in an amount by volume of at least 40%, preferably at least 45%, The ceramic reinforcement of the shell covers the largest part of the outer surface of the grinding ball, except for a small surface formed by one or two inflow holes.
Claims
1. A composite grinding ball having a core-shell structure, wherein the shell of the core-shell structure comprises a ceramic reinforcement, and the ceramic reinforcement comprises: a three-dimensional interconnected network of periodically alternating ceramic-metal composite particles and interstices, the ceramic-metal composite particles and interstices having an average size in the millimeter range; The ceramic-metal composite particles comprise at least 40 volume %, preferably at least 60 volume %, and most preferably at least 70 volume % of ceramic particles, the ceramic particles being bonded in a binder metal matrix, the ceramic particles having an average size in the micrometer range; A three-dimensional interconnected network of ceramic-metal composite particles and interstices is embedded in a ferroalloy cast metal matrix, wherein the ferroalloy cast metal matrix fills interstices between the interconnected ceramic-metal composite particles of the three-dimensional interconnected network; The ceramic-metal composite particles embedded in the ferrous alloy cast metal matrix have a porosity of the following volume fraction: less than 5 volume%, preferably less than 3 volume%, most preferably less than 1 volume%, the porosity measurement is based on ISO 13383-2:2012 Annex A; The shell comprises the following volume content of ceramic-metal composite particles: at least 35 volume %, preferably at least 45 volume %; The ceramic reinforcement of the shell covers at least 85%, preferably 90%, most preferably 95% of the total surface of the grinding ball.
2. The composite grinding ball according to claim 1, wherein the ceramic particles are selected from carbides, nitrides, carbonitrides and borides or mixtures thereof.
3. The composite grinding ball according to claim 1 or 2, wherein the ceramic particles are selected from the group consisting of titanium carbide, titanium carbonitride, tungsten carbide, niobium carbide, tantalum carbide, vanadium carbide, zirconium carbide, hafnium carbide and molybdenum carbide.
4. Composite grinding ball according to any one of the preceding claims, wherein the thickness of the ceramic reinforcement shell is in the range of 2 to 15 mm, preferably 2 to 10 mm, most preferably 3 to 8 mm.
5. The composite grinding ball according to any one of the preceding claims, wherein the embedded ceramic-metal composite particles have a particle size volume distribution between 0.3 and 10 mm and an average particle size D between 1 and 4 mm, preferably between 1 and 3 mm. 50 , and wherein the average particle size D can be measured by microscopic observation using a computer program and an optical microscope 50 , such that there are at least 250 ceramic-metal composite particles in the field of view of one or more polished cross-sections of one or more samples, wherein an appropriate threshold allows for subdivision of the particles in the grayscale image and the background.
6. A composite grinding ball according to any one of the preceding claims, wherein the particle size of the bonded ceramic particles in the binder metal matrix is 0.1 to 50 μm, preferably 0.1 to 30 μm, and the average particle size D 50 It is 0.5 to 20 μm, preferably 1 to 10 μm.
7. The composite grinding ball according to any one of the preceding claims, wherein the binder metal matrix is selected from the group consisting of iron-manganese based alloys, iron-chromium based alloys and nickel based alloys.
8. The composite grinding ball according to any one of the preceding claims, wherein the ferroalloy cast metal matrix comprises high chromium white cast iron or steel, the high chromium white cast iron comprising at least 11 wt. % chromium.
9. A method for manufacturing a composite grinding ball as claimed in claims 1 to 8, comprising the following steps: a) providing or producing a ceramic-metal composite particle, the ceramic-metal composite particle comprising at least 40% by volume of micron-sized ceramic particles, the micron-sized ceramic particles being bonded in a binder metal matrix, the ceramic-metal composite particle having a porosity of less than 5% by volume, preferably less than 3% by volume, in particular less than 1% by volume; b) manufacturing a ceramic preform shell, preferably in the form of a half shell, which is a three-dimensional interconnected network of millimeter-sized ceramic-metal composite particles obtained in step a) and millimeter-sized gaps that are periodically alternating; c) assembling the shells obtained in step b) into a hollow sphere comprising one or two inflow openings and placing the hollow sphere in the cavity of a mold for the grinding balls to be cast; d) casting a metal matrix from an iron alloy, casting the grinding balls and simultaneously infiltrating the millimeter-scale interstices of the three-dimensional interconnected network of shells positioned according to step c); e) demoulding the composite grinding balls.
10. The method for manufacturing a composite grinding ball according to claim 9, wherein the manufacturing process of the ceramic-metal composite particles in step a) comprises: - grinding a powder composition comprising ceramic particles and a binder metal matrix in the presence of a solvent; - mixing 1 to 10%, preferably 1 to 6%, of wax into the powder composition; - Removal of the solvent by drying to obtain an agglomerated powder; - Pressing the agglomerated powder into strips, sheets or rods; - Crushing of strips, sheets or rods into particles in the millimeter size range; - Sintering the ceramic metal particles in a vacuum or inert atmosphere furnace at a temperature of 1200-1600° C. until a porosity of less than 5%, preferably less than 3%, even less than 1% by volume is reached.
11. The method according to claim 10, wherein the step of grinding the powder composition comprising ceramic particles and a binder metal matrix in the presence of a solvent is carried out until an average particle size D of 1 to 20 μm, preferably 1 to 10 μm, is obtained. 50 The particle size of the powder is measured by laser diffraction using the MIE theory according to the guidelines given in ISO13320:2020, where the refractive index and absorptivity are adapted to the ceramic particles, the obscuration is in the range of 10 to 15%, and the weighted residual is less than 1%.
12. The method according to claim 10 or 11, wherein the particle size of the sintered particles crushed from the strip, sheet or rod is 0.3 to 10 mm, preferably 0.4 to 6 mm, and the average particle size D 50 Selected from 1 to 6 mm, preferably 1 to 3 mm, the particle size is measured by dynamic image analysis according to ISO 13322-2:2006, or sieved according to ISO 4497:2020.
13. The method for manufacturing a composite grinding ball according to claim 10, wherein step b) comprises the following steps: - mixing the ceramic-metal composite particles obtained according to claim 8 with about 0.5 to 7% by weight, preferably 1 to 4% by weight, of a binder, preferably an organic binder; - pouring the mixture into a shell mold and compacting; - Drying the mixture at a suitable temperature and time to remove the solvent of the glue or to achieve curing by coagulation or catalyst; - De-molding the dried mixture and obtaining a shell of a three-dimensional interconnected network of periodically alternating millimeter-sized ceramic-metal composite particles and millimeter-sized gaps to assemble into a hollow preform positioned in a composite grinding ball mold.
